Looking for the Self in Pathological Unconsciousness - Demertzi, Athena; Vanhaudenhuyse, Audrey; Bredart, Serge; Heine, Lizette; Di Perri, Carol; Laureys, Steven (Frontiers in Human Neuroscience, 2013)
There is an intimate relationship between consciousness and the notion of self. By studying patients with disorders of consciousness, we are offered with a unique lesion approach to tackle the neural correlates of self in the absence of subjective reports. Studies employing neuroimaging techniques point to the critical involvement of midline anterior and posterior cortices in response to the passive presentation of self-referential stimuli, such as the patient’s own name and own face. Also, resting state studies show that these midline regions are severely impaired as a function of the level of consciousness. Theoretical frameworks combining all this progress surpass the functional localization of self-related cognition and suggest a dynamic system-level approach to the phenomenological complexity of subjectivity. Importantly for non-communicating patients suffering from disorders of consciousness, the clinical translation of these technologies will allow medical professionals and families to better comprehend these disorders and plan efficient medical management for these patients.